Uji Efektivitas Konsentrasi Spodoptera litura – Nuclear Polyhedrosis Virus (SlNPV) JTM 97C Formulasi Bubuk Terhadap Larva Spodoptera litura Fabricius (Lepidoptera: Noctuidae) Pada Tanaman Kedelai - M Novel Ghufron Syahroni; Nanang Tri Haryadi (Jurnal Pengendalian Hayati, 2019)
Spodoptera litura (armyworm) is an important leaf pest that is polyphagic and has a broad range of hosts. Spodoptera litura is the main pest in soybean plants and can cause up to 50% damage and often results in decreased productivity and even crop failure. Spodoptera litura is widespread in areas with hot and humid climates from the subtropics to the tropics. S. litura pests attack cultivation plants in the vegetative and generative phases. The prospect of insect pathogens as a substitute for chemical insecticides is quite good in terms of their effectiveness and impact on the environment. Nuclear Polyhedrosis Virus (NPV) is one of the Baculoviridae viruses that infect the larval stage. Spodoptera litura Nuclear Polyhedrosis Virus (SlNPV) is a pathogenic virus that infects armyworms. SlNPV JTM 97C is an effective isolate in controlling larvae of Spodoptera litura. The larvae used in this study were larval instar 4, instar 5, and instar 6. The study was conducted using a Completely Randomized Design (CRD) with 6 treatments and 3 replications. The treatments consisted of controls, 1 g / l, 2g / l, 3 g / l, 4 g / l, and 5 g / l. Each treatment was applied to instar 4, instar 5 and 6 instar larvae. The results showed that SlNPV JTM 97C affected mortality, stopped eating and pupa formation of instar 4, instar 5 larvae, but did not affect instar 6 larvae. The younger the larval instar the higher the pathogenicity response.